QT interval prolongation and rhabdomyolysis associated with diphenhydramine toxicity: a case report. Issue 2 (3rd March 2020) - Ali, Zain; Khan, Mariya; Ullah, Waqas; Kpehor, Atsoufui A.; Cheema, Muhammad Arslan
ABSTRACT: Diphenhydramine is a widely available, over-the-counter medication used for allergies and as a sleeping aid. When used in prescription doses, it is generally safe. Overdose of the medication has been associated with dangerous and life-threatening outcomes. Our case describes diphenhydramine toxicity manifesting with two rare but potentially life-threatening complications, rhabdomyolysis, and QT prolongation. Laboratory testing for diphenhydramine levels are not widely available. We recommend a high degree of suspicion for these complications when evaluating patients with diphenhydramine overdose, to adequately manage and prevent untoward outcomes.